Genus-2 holographic correlator on AdS5 × S5 from localization - Chester,SM (Journal of High Energy Physics, 2020)
A bstract We consider the four-point function of the stress tensor multiplet superprimary in $$ \mathcal{N} $$ N = 4 super-Yang-Mills (SYM) with gauge group SU( N ) in the large N and large ’t Hooft coupling $$ λ \equiv {g}_{YM}^2N $$ λ ≡ g YM 2 N limit, which is holographically dual to the genus expansion of IIB string theory on AdS 5 × S 5 . In [1] it was shown that the integral of this correlator is related to derivatives of the mass deformed $$ \mathcal{N} $$